Localization dynamics of endogenous fluorescently labeled RAF1 in EGF-stimulated cells - Surve, Sachin V. (Mol Biol Cell, 2019)
Activation of the epidermal growth factor (EGF) receptor (EGFR) at the cell surface initiates signaling through the RAS-RAF-MAPK/ERK1/2 pathway and receptor endocytosis. Whether this signaling continues from endosomes remains unclear, because RAS is predominantly located on the plasma membrane, and the localization of endogenous RAF kinases, downstream effectors of RAS, is not defined. To examine RAF localization, we labeled endogenous RAF1 with mVenus using gene editing. From 10 to 15% of RAF1-mVenus (<2000 molecules/cell), which was initially entirely cytosolic, transiently translocated to the plasma membrane after EGF stimulation. Following an early burst of translocation, the membrane-associated RAF1-mVenus was undetectable by microscopy or subcellular fractionation, and this pool was estimated to be <200 molecules per cell. In contrast, persistent EGF-dependent translocation of RAF1-mVenus to the plasma membrane was driven by the RAF inhibitor sorafenib, which increases the affinity of Ras-GTP:RAF1 interactions. RAF1-mVenus was not found in EGFR-containing endosomes under any conditions. Computational modeling of RAF1 dynamics revealed that RAF1 membrane abundance is controlled most prominently by association and dissociation rates from RAS-GTP and by RAS-GTP concentration. The model further suggested that the relatively protracted activation of the RAF-MEK1/2-ERK1/2 module, in comparison with RAF1 membrane localization, may involve multiple rounds of cytosolic RAF1 rebinding to active RAS at the membrane.